PENGARUH PMR TERHADAP HASIL BELAJAR SISWA KELAS III DI SDN 38PONTIANAK UTARA - Marrino, Marrino; Hamdani, Hamdani; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyze whether there is not the effect of RME for third grade SDN 38 north Pontianak. The research method used is the experimental method with the experimental form Pre Experimental Design, experimental design One Group Pretest-Posttest Design. The population in this study were all third grade students public elementary school 38 north Pontianak with a total of 55 students. The sample selection was done by purposive sampling type, with the results of the sample being third grade B. The data collection tool was in the form of a test of student learning outcomes with 4 essay questions. Based on statistical calculations from the average results of third grade B pre-test of 46.30 and the average post-test results of third grade B of 78.30 obtained tcount of 22.19 and ttable Î± = 5% (with dk = 6 - 3 = 3) of 2.060 which means tcount (22.19)>ttable (2.060). So, it can be concluded that there were significant differences in student learning outcomes in the material determining the circumference and area of square and rectangle, between students taught before applying RME, and groups of students taught by applying RME in third grade SDN 38 north Pontianak.Keywords: Effect, Learning Outcome, Realistic Mathematic EducationAbstractThis study aimed to analyze whether there is not the effect of RME for third grade SDN 38 north Pontianak. The research method used is the experimental method with the experimental form Pre Experimental Design, experimental design One Group Pretest-Posttest Design. The population in this study were all third grade students public elementary school 38 north Pontianak with a total of 55 students. The sample selection was done by purposive sampling type, with the results of the sample being third grade B. The data collection tool was in the form of a test of student learning outcomes with 4 essay questions. Based on statistical calculations from the average results of third grade B pre-test of 46.30 and the average post-test results of third grade B of 78.30 obtained tcount of 22.19 and ttable Î± = 5% (with dk = 6 - 3 = 3) of 2.060 which means tcount (22.19)>ttable (2.060). So, it can be concluded that there were significant differences in student learning outcomes in the material determining the circumference and area of square and rectangle, between students taught before applying RME, and groups of students taught by applying RME in third grade SDN 38 north Pontianak.Â Keywords: Effect, Learning Outcome, Realistic Mathematic Education